THE APPLICATION OF MERRY GO AROUND TECHNIQUE IN DEVELOPING THE STUDENTS’ READING ABILITY (A COLLABORATIVE CLASSROOM ACTION RESEARCH TO THE SECOND YEAR STUDENTS OF MTSN DEWANTARA): THE APPLICATION OF MERRY GO AROUND TECHNIQUE IN DEVELOPING THE STUDENTS’ READING ABILITY (A COLLABORATIVE CLASSROOM ACTION RESEARCH TO THE SECOND YEAR STUDENTS OF MTSN DEWANTARA) - misnawati; Zuraini; Ulfa Maszura (Journal of English Education and Social Science, 2022)
The title of this research is The Application of Merry Go Around Technique In Developing the Students’ Reading Ability (A Collaborative Classroom Action Research to the Second Year Students of MTsN Dewantara). The problems of this research are: 1)How does Merry Go Arround technique can improve the students’ ability in mastering reading of the second year students of MTsN Dewantara?. 2) How does Merry Go Arround technique can improve the students’ motivation of MTsN Dewantara in learning reading?. The Purpose of the Research are : 1) To know how the Merry Go Arround technique can improve the students’ ability in mastering reading of the second year students of MTsN Dewantara. 2) To know how the Merry Go Arround technique can improve the students’ motivation in learning reading of MTsN Dewantara in learning reading. Reading is defined as the level of understanding of writing. Proficient reading depends on the ability to recognize words quickly and effortlessly. Merry Go Around technique is the way to generate the activity and should answering the question inform of around and compounding the way of hand our. The methodology of this research is Collaborative Classroom Action Research; the setting of this research was MTsN Dewantara. The sample of this research was the second year students of class VIII/C which total students was 30 students. The instruments used in this research are: test, observation sheet, questionnaire, and field note. The result of this research are: the answer of the first problem was, the students’ ability in mastering reading by using Merry go Around technique improved, it showed by increased of the first cycle was 62, but it did not find the criteria of succes, so the resarcher continued to next cycle and the researcher found 76. It meant the students’ score improve significantly. The result of questionnaire also in level 3 by the range score 3.9 and 3.8. It meant that the students had positive response toward Merry go Around technique in improving reading. It could be seen from the result of questionnaire analysis that consisted in number 3.8 and 3.9. It stood in the criteria of the success. So that, the researcher concluded that the students were happy and their motivation improved.